Activated charcoal in the in vitro establishment of raspberry cultivars (Revista de Ciências Agroveterinárias, 2018)
Propagation of raspberry (Rubus idaeus L.) is usually performed from root cuttings. Although fruits have viable seeds, sexual reproduction is unwanted due to the high genetic variability and long juvenile period besides dormancy, which causes plant development to be slow and consequently produces the same result in the production of new seedlings. So, in vitro micropropagation is a viable technique for seedling production, thus maintaining genetic features of the mother plant, uniformity, precocity of production, as well as accelerating the conventional propagation methods, are an alternative to planters. The aim was the evaluation of the effect of different concentration ratios of activated charcoal supplied in the growth medium on the different raspberry cultivars. Activated charcoal was used (0; 2; and 4 g L-1), and the raspberry cultivars were (Indian Summer, Heritage, Willamette, Golden Bliss, Polana, Fallgold, Schönemann, and Bababerry). The best oxidation control was presented on cultivars Golden Bliss, Polana, Fallgold, Schönemann, and Bababerry, grown on cultivation medium added of 4 g L-1 activated charcoal, due to the absorption of phenolic compounds released into the culture medium.
Keywords: Rubus idaeus; oxidation; phenolic compounds; Rubus; antioxidants